Job Pressure and SES-contingent Buffering: Resource Reinforcement, Substitution, or the Stress of Higher Status?. (June 2015) - Koltai, Jonathan; Schieman, Scott
Analyses of the 2008 National Study of the Changing Workforce demonstrate that job pressure is associated with greater anxiety and job dissatisfaction. In this paper we ask, What conditions protect workers? The conventional buffering hypothesis in the Job-Demands Resource (JD-R) model predicts that job resources should attenuate the relationship. We test whether the conventional buffering hypothesis depends on socioeconomic status (SES). Support for conventional buffering is evident only for job dissatisfaction—and that generalizes across SES. When anxiety is assessed, however, we observe an SES contingency: Job resources attenuate the positive association between job pressure and anxiety among workers with lower SES, but exacerbate it among those with higher SES. We discuss the implications of this SES-contingent pattern for theoretical scenarios about "resource reinforcement, " "resource substitution, " and the "stress of higher status." Future research should consider SES indicators as potential contingencies in the relationship between job conditions and mental health.